2005
DOI: 10.2174/156652405774962335
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo Hemorrhagic Fever Virus

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is an important human pathogen, which is the cause of a tick-borne illness occurring in many areas of Africa, Asia, and Europe. CCHF is characterized by a sudden onset of high fever, chills, and severe headache. Other symptoms can include gastrointestinal disorders, such as nausea, vomiting, and diarrhea. In severe cases, hemorrhagic manifestations can occur and often present as large areas of ecchymosis, rather than frank bleeding. Exposure to ticks, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 87 publications
0
45
0
Order By: Relevance
“…A new immunoglobulin, Venin, which is specific to CCHFV, has been prepared from the plasma pool of boosted donors through ethanol-polyethylene glycol fractionation and an ion-exchange purification step (65). However, in the case of CCHFV, the beneficial effects of immunotherapy are extremely limited (20,66).…”
Section: Treatmentmentioning
confidence: 99%
“…A new immunoglobulin, Venin, which is specific to CCHFV, has been prepared from the plasma pool of boosted donors through ethanol-polyethylene glycol fractionation and an ion-exchange purification step (65). However, in the case of CCHFV, the beneficial effects of immunotherapy are extremely limited (20,66).…”
Section: Treatmentmentioning
confidence: 99%
“…structure biology | virology C rimean-Congo hemorrhagic fever virus (CCHFV) is a tickborne virus and the causative agent of Crimean-Congo hemorrhagic fever (CCHF), a severe human disease that occurs in over 30 countries in Asia, the Middle East, Southeastern Europe, and Africa (1,2) and results in high mortality. There is currently no vaccine against CCHF and available therapeutic interventions are limited.…”
mentioning
confidence: 99%
“…The high pathogenicity of CCHFV has led to it being considered as a severe public health threat and a potential bioterrorism agent in the wider world. It is therefore classified as a World Health Organization biosafety level 4 pathogen, limiting fundamental investigations in the laboratory (2).…”
mentioning
confidence: 99%
“…In the absence of a vaccine and effective antivirals, only palliative treatment is available for this disease (Soares-Weiser et al, 2010a, b). Therefore, the World Health Organization has indicated that CCHFV should be handled only in Biosafety Level 4 facilities (Flick & Whitehouse, 2005).…”
Section: Introductionmentioning
confidence: 99%